The effect of weaning age and feeding of different calf starter rations on testicular growth and body weight of Borena-Friesian crossbred bull calves - Gojam, Y.; Tegegne, Azage; Gebrewold A.; Bekele, T. (2004)
An experiment was conducted to determine the effects of feeding different calf starter rations, weaning age and their interactions on testicular growth and body weight of Borena Friesian (BF) crossbred bull calves at the age of 105 (closer to weaning) and 202 (nearly 6 months) days. Statistical analysis indicated no significant differences (p>0.05) in values obtained in testes diameter (TD) and scrotal circumference (SC) at both ages. There was, however, significant (p<0.05) and positive correlation between testes measurements and the body weight of bull calves. The result of this study suggests that Borena Friesian crossbred calves can successfully be weaned as early as seven weeks of age, provided that they are supplied with easily digestible solid feeds enough to support the protein and energy requirements of the growing calves. Adequate supply of proper solid feed both at pre and post weaning period, is believed to over come any adverse effect encountered during the pre-weaning period, through compensatory growth effect. Other aspects of rearing future bulls such as the effects of feed and other environmental factors on semen characteristics could be the subject of further study.